1982
DOI: 10.1111/j.1365-2133.1982.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium hydroxide granulomas: light and electron microscopic studies and X-ray microanalysis

Abstract: Three children are described in whom painful subcutaneous nodules developed 1-2 years after the injection of adsorbed diphtheria, tetanus and pertussis vaccine. The diagnosis of aluminium hydroxide granuloma was established by ultrastructural examination with X-ray microanalysis.Mild cutaneous reactions frequently occur with adsorbed diphtheria, tetanus and pertussis (DTP) vaccines (Burland et al, 1968). Persistent nodules are seen less commonly, but previous histological studies have suggested a localized res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
3

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 3 publications
6
39
0
3
Order By: Relevance
“…The pruritic nodules, which lasted for many years and caused considerable discomfort, were, in 77% of the cases, associated with hypersensitivity to Al, as demonstrated by an epicutaneous test. Previously, not more than about 100 cases of persistent pruritic nodules at the injection site of Al-adsorbed vaccines had been reported in the literature since 1960, most commonly after diphtheria-tetanus (DT), pertussis and hepatitis B vaccines [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The pruritic nodules, which lasted for many years and caused considerable discomfort, were, in 77% of the cases, associated with hypersensitivity to Al, as demonstrated by an epicutaneous test. Previously, not more than about 100 cases of persistent pruritic nodules at the injection site of Al-adsorbed vaccines had been reported in the literature since 1960, most commonly after diphtheria-tetanus (DT), pertussis and hepatitis B vaccines [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In these cases, histopathologic studies of skin lesions revealed either a histiocytic foreign body reaction, mostly in early lesions, 7,8 or a lymphoid infiltration showing a granulomatous reaction with or without necrosis, sometimes with the presence of eosinophilic crystalline material. [2][3][4][5][6]9,10 Cutaneous lymphocytomas, also called cutaneous lymphoid hyperplasia (CLH), are benign cutaneous infiltrates predominantly composed of B cells showing a follicular architecture. 11 They belong to the spectrum of cutaneous pseudolymphomas, defined as B and/or T lymphocytic infiltrates of the skin exhibiting clinical and/or histopathologic features that mimic those of cutaneous lymphomas, but differing from this latter entity by their benign course.…”
mentioning
confidence: 99%
“…109 The aluminum can be confirmed by x-ray microanalysis or by the solochrome azurine stain, in which crystals of aluminum salts stain a deep gray-blue color. 110 Skin biopsies of aluminum tattoos after the topical application of aluminum chloride show individual and clusters of histiocytes containing round to slightly indented single nuclei with abundant basophilic or occasionally amphophilic granules. Granules vary slightly in size and shape and measure up to 1 to 2 mm in diameter and correspond to aluminum particles.…”
Section: Mineral and Metallic Particles Aluminummentioning
confidence: 99%